2022
DOI: 10.5114/ceji.2022.112993
|View full text |Cite
|
Sign up to set email alerts
|

Novel therapies for diabetic retinopathy

Abstract: diabetes mellitus (dM) is a metabolic disease characterized by high blood glucose levels as well as microvascular and macrovascular changes. according to the latest statistics the growth of dM incidence is very fast. Diabetic retinopathy (Dr) -one of the common DM complications -is the leading cause of blindness among professionally active people. traditional treatment of dR including drugs controlling hyperglycemia, laser therapy, vitrectomy, and intravitreal injections of anti-Vegf is effectively administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 53 publications
0
4
0
4
Order By: Relevance
“…DM is one of the most significant public health concerns, estimated to be affecting over 570 million people by 2025 [ 105 ]. It consists of a group of conditions characterised by impaired glucose metabolism caused by insulin secretion deficiency and/or its biological function disorder, resulting in hyperglycaemia and several vascular complications [ 106 ]. DR is the most common complication of DM, estimated to be present in more than 103 million people worldwide, and ranking as one of the leading causes of preventable blindness in the working-age population [ 107 ].…”
Section: Diabetic Retinopathy and Diabetic Macular Edemamentioning
confidence: 99%
See 1 more Smart Citation
“…DM is one of the most significant public health concerns, estimated to be affecting over 570 million people by 2025 [ 105 ]. It consists of a group of conditions characterised by impaired glucose metabolism caused by insulin secretion deficiency and/or its biological function disorder, resulting in hyperglycaemia and several vascular complications [ 106 ]. DR is the most common complication of DM, estimated to be present in more than 103 million people worldwide, and ranking as one of the leading causes of preventable blindness in the working-age population [ 107 ].…”
Section: Diabetic Retinopathy and Diabetic Macular Edemamentioning
confidence: 99%
“…As the disease progresses to proliferative DR, neovascularisation and vitreous or preretinal haemorrhage are observed, which can lead to retinal detachment and subsequent blindness [ 104 , 106 ]. The disease has a slow onset and gradual progression, affected by several risk factors, including glycaemic control, hypertension, hyperlipidaemia, obesity, duration of DM, puberty, and pregnancy [ 111 ].…”
Section: Diabetic Retinopathy and Diabetic Macular Edemamentioning
confidence: 99%
“…(2) Therapeutic drugs. Due to the limitations of traditional surgical treatment [24] , in recent years, drugs with less side effects and longer curative effects for the treatment of DR have been developed, including drugs for targeted therapy, mesenchymal stem cell injection, SGLT2 inhibitors etc. AI et al [25] conducted animal experiments on Xiao Bopi(XBP) with the efficacy of clearing away heat and toxic materials, and showed that XBP effectively improved the glucose tolerance and insulin sensitivity of DR mice, while markedly thickened the retinal of DR mice.…”
Section: Research Trendsmentioning
confidence: 99%
“…Empagliflozin (EMPA), an aSGLT-2 inhibitor drug known for its high selectivity for SGLT2, is the first-choice glucose-lowering agent that can significantly reduce cardiovascular risk in patients with T2DM [ 80 ] and may also help in diabetic retinopathy treatment [ 81 , 82 ]. Gong et al showed that EMPA can lower BCAA levels in DR by boosting BCAA catabolism through an increase in BCAT levels and via BCKDK inhibition, which leads to BCKDH complex activation and may play a protective role in ameliorating the damaging effects of DR [ 83 ].…”
Section: Therapeutic and Biomarker Potential Of Bcaasmentioning
confidence: 99%